The Cryptoanarchist Character of Bitcoin's Digital Governance. - Beltramini, Enrico (Anarchist Studies, 2021)
This article investigates the intellectual assumptions behind cryptoanarchist models of digital governance produced by certain technologies such as Bitcoin and Blockchain. While Bitcoin and the blockchain technologies that come with it have generated broad interest, most attention has been focused on matters of finance (Bitcoin the cryptocurrency) and technology (Bitcoin the platform). In this article, the target is narrowed to the discourses of autonomy and anonymity to describe the ideological commitments lying behind cryptoanarchist forms of organisation and their anti-technocratic sentiments. The notion of distributed trust at the core of the political theory of cryptoanarchist governance has implications that transcend the tiny boundaries of Bitcoin.